Gamma Radiation Induced Contraction of Alkyne Modified Polymer Hydrogels. Issue 3 (5th November 2021) - Brevé, Tobias G.; Liu, Huanhuan; Denkova, Antonia G.; Eelkema, Rienk
Abstract: Gamma radiation triggered secondary crosslinking of dextran hydrogels leads to macroscopic hydrogel contraction. The authors use stable polymer hydrogels, prepared through azide‐alkyne crosslinking, containing surplus alkyne groups. γ ‐irradiation of these gels leads to more alkyne crosslinking, enabling controlled increase of crosslink density, which in turn leads to an increase of hydrogel stiffness and macroscopic hydrogel contraction. Gel contraction scales linearly with the applied radiation dose. The same mechanism is applied to achieve γ ‐radiation triggered release of the small molecule cargo, akin to wringing out a sponge. γ ‐irradiation of touching hydrogel objects leads to gel fusion and the formation of a self‐supporting gel connection, demonstrating the reactivity of the excess alkyne groups. They envision applications in gel gluing and the construction of complex gel architectures, as well as in responsive materials for controlled release. Abstract : This study reports a gamma radiation induced secondary crosslinking strategy to translate molecular reactivity to macroscopic motion in dextran‐based hydrogels. The ionizing radiation trigger can initiate fusion of separate hydrogel objects, and macroscopic hydrogel contraction resulting in the excretion of a loaded cargo.